A study on gold investment in Public Gold / Nur Zalina Ahmad Zahri - Ahmad Zahri, Nur Zalina (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
This research is focused on the gold investment which comply to Shariah in one of certified and authorized gold investment company in Malaysia, which is Public Gold. This company has several branches such as in Kuala Lumpur, Selangor, Perak, Penang and Kedah. The main focus to study in this paper is about Shariah management in gold investment which bring confuse to people about how does the Shariah work in this kind of investment. Many researcher has define about the gold investment and even the financial expert is agreed with the use of gold since it has many advantages that contribute to the owner, and country. In Islam, gold has been implemented since the era of Prophet Muhammad pbuh and until now the gold is remain it strong and high value. Unfortunately the use and it benefit however not really be seen to people since they think that gold has expensive value and quite hard to buy it. Yet, they think the gold is not been applicable in any transaction and there is no benefit to get the gold as their asset. In addition, this paper is generally focus about the common gold investment but also mentioned the procedure and use in Public Gold. The gold investment has been selected as an issue is because since the gold is one of the ribawi item, so it important to investor know about the gold investment whether it is contradict to Shariah or not. Public Gold has implement all Shariah ruling in their transaction and gold investment procedure. They has set up an affordable price for the beginner in order to encourage people to join the gold investment regarding to people perspective about it high price and functionless in transaction this while. Gold investment however is practiced as long term investment and as a saving to the investor himself so he able to stabilize his economy if the country disrupted. This research paper based to qualitative method since the content analysis and interview were used at Public Gold in Bandar Sunway, Petaling Jaya, Selangor. The study utilized the books, journals and document given by the Public Gold as certified gold investment Shariah-compliance. The research study done has created only several different between gold investment of Shariah and conventional practice based on their transaction. However, the physical gold is truly defined as Shariah manner when it exist during the contract is dealing.